The role of social scientific issues and outdoor activities in primary students and teachers perceptions in inquiry-based science learning - Boaventura, D.M. (2021)
Climate change is one of the major challenges facing society today and more effective education is needed on this topic. This study analysed the effects of an inquiry-based science activity about climate change effects in ocean ecosystems, done in a research laboratory and in the classroom, on primary students’ knowledge, investigation skills and satisfaction. Data were collected through the application of pretests and posttests, direct observation, questionnaires, interviews and document analysis. Results revealed an increase in students’ scientific knowledge and application to new situations. Regarding investigation skills, all students were able to make predictions, and to easily observe and register data. However, experimental planning and conclusions were more difficult for them. Students and teachers emphasised their satisfaction with the outdoor activity, teamwork and the subject. The present study revealed a positive effect of the participation in the inquiry-based activity, embedded on a socio-scientific issue, in students’ conceptual knowledge and in the development of investigation skills.